The Flower Princess - Brown, Abbie Farwell, 1871-1927 (Salt Lake City, UT : Project Gutenberg, 2010)
"The Flower Princess" by Abbie Farwell Brown is a children's fantasy written in the early 20th century. This enchanting tale follows Princess Fleurette, a beautiful girl who lives in a magical garden full of flowers and delights. The story centers around her love for flowers and the quest of various princes who seek her affection, as she challenges them to find her favorite flower as a test of love. At the start of the story, we are introduced to Princess Fleurette and her magnificent garden, which is both a peaceful sanctuary and a place of beauty. While many princes come to court her, she playfully tells them that she will only choose a suitor who can correctly guess her favorite flower hidden among the blooms. Each prince leaves disappointed after failing to find it. One fateful morning, Fleurette meets a wandering minstrel named Joyeuse in her garden, and they quickly form a bond through their shared love of flowers. As they play together, Fleurette's unique charm and mischief come to life, hinting at adventures to come. (This is an automatically generated summary.)
The flower princess -- The little friend -- The mermaid's child -- The ten blowers.
Release date is 2010-05-02
E-text prepared by Suzanne Shell, Emmy, and the Project Gutenberg Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://www.archive.org/details/americana)
Keywords: Fairy tales; Children's stories; Friendship -- Juvenile fiction; Princesses -- Juvenile fiction; Courtship -- Juvenile fiction; Mermaids -- Juvenile fiction